PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG, DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN PADA SUB SEKTOR PERDAGANGAN BESAR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - Dewi Martha Sofia; Lena Farida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aimed to determine the effect of dividend policy, debt policy and investment decisions of the Company value in the Sub Sector wholesale listed in Indonesia Stock Exchange study period of 2010 - 2014. The independent variables Dividend Policy are the indicators dividend Payout Ratio (DPR), Debts policy with indicators Debt to Equity Ratio (DER), and Investment Decisions with indicators of Price Earning Ratio (PER). While that is used as the dependent variable is the value the company at indikatorkan Price to Book Value (PBV). The method used to observe the effect of Dividend Policy, Debt Policy and Investment Decisions to the company Value is using multiple linear regression.This study uses secondary data from financial statements of companies. Samples and sampling using purposive sampling techniques. Classic assumption test in this study include normality test, multicollinearity test, heterocedasticity test and autocorrelation test. Analysis of data using multiple linear regression analysis, t test, F test, and test the coefficient of determination. Analysis of data using multiple linear regression analysis with SPSS 16.The results showed that the variables DPR and DER partially (t test) did not significant effect on the PBV on wholesale sub sector listed on the Indonesia Stock Exchange, while the variable PER significant effect on the PBV on wholesale sub sector listed in Indonesia Stock Exchange. The results of simultaneous (f test) showed a significant effect of the variable DPR, DER, and PER to PBV on the wholesale sub sector registered in the Indonesia Stock Exchange.Keywords: Dividend Policy, Debt Policy, Investment Decision, Company Value